2005
DOI: 10.1002/macp.200400467
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(urethane acrylate‐co‐styrene) Films Containing Silver Nanoparticles by a Simultaneous Copolymerization/in situ Electron Transfer Reaction

Abstract: Summary: A novel process for the synthesis of nanocomposite films containing silver nanoparticles is presented. Unlike conventional synthetic processes, silver nanoparticles and the polymer film constituting the nanocomposite film were synthesized simultaneously through an in situ electron transfer reaction and the copolymerization of styrene and amphiphilic urethane acrylate nonionomer (UAN), which contains hydrophobic poly(propylene oxide) segments and hydrophilic poly(ethylene oxide) segments along the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Synthesis procedure and molar ratio of UAN chain was described in detail in our previous reports. [23][24][25] The polystyrene equivalent molecular weight of synthesized UAN chains is a 6700 (g/mol) weight average molecular weight with a polydispersity of 1.93. Expected molecular structure of UAN chain was schematically illustrated in Figure 1.…”
Section: Synthesis Of Uanmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis procedure and molar ratio of UAN chain was described in detail in our previous reports. [23][24][25] The polystyrene equivalent molecular weight of synthesized UAN chains is a 6700 (g/mol) weight average molecular weight with a polydispersity of 1.93. Expected molecular structure of UAN chain was schematically illustrated in Figure 1.…”
Section: Synthesis Of Uanmentioning
confidence: 99%
“…[23][24][25] Each reaction was performed in a 500 mL four-neck vessel equipped with stirrer, thermometer, and an inlet system for nitrogen gas. Synthesis procedure and molar ratio of UAN chain was described in detail in our previous reports.…”
Section: Synthesis Of Uanmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon increasing the irradiation time, the absorption band of EO 2-is progressively collapsing, however we fail to observe the formation of silver nanoparticles. The same photolysis experiment is performed with a solution of acetonitrile containing eosin dye, AgNO 3 [55][56][57][58][59]. For instance, it has been reported that the photogenerated alkoxy benzyl radicals [33] or ketyl radicals [60] can convert efficiently Ag + to Ag 0 .…”
Section: Mechanistic Aspect Of Ag Nanoparticles Photogeneration In Somentioning
confidence: 99%
“…The change of reflectivity19]. After many experiments at different speeds, the optimal flow speed was 2.5 mL/min with reaction time 30 s. The results were shown inFig.…”
mentioning
confidence: 99%